PENGEMBANGAN PRODUK OLAHAN DURIAN DALAM MENDUKUNG KAMPUNG BATU BUSUK KELURAHAN LAMBUNG BUKIK KECAMATAN PAUH SEBAGAI DAERAH WISATA - Risa Meutia Fiana; P.K. Dewi Hayati (LPPM Universitas Andalas, 2022)
The development of Batu Busuk into an agro-tourism area is the existence of people's durian plantations which are cultivated in a sub-system. Durian is known as one of Indonesia's tropical exotic fruit plants with a delicacy of taste and a certain aroma that is nicknamed the king fruit. The high potency of durian should expose Batu Busuk as a durian village that sells fresh durian fruit and diversified durian processed products such as durian ice cream, durian dodol, durian pancakes, and frozen durian to support tourism development. A SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) needs to be carried out to assess the potency of the development of durian processed products in supporting Batu Busuk village as a tourist destination. This community service activity took place in Batu Busuk village, Lambung Bukit sub-district, Pauh sub-district, Padang Municipality. Partners in this activity are PKK Kampung Batu Busuk. The purpose of this activity is to develop Kampung Batu Busuk into a tourist area which is supported by the development of processed durian products as a tourism attraction. Based on a SWOT analysis qualitatively of the potency of durian processed products development, it can be concluded that durian processed products have a great prospect of supporting the development of Batu Busuk Village as a tourist destination. The strategy offered is to apply the strategy of product development, product market development, improvement of tourism management, and development of managers, especially PKK community in Batu Busuk village. One way to achieve this strategy is by collaborating with the people of Kampung Batu Busuk and Andalas University in the development of processed durian products as a supporter of tourist attractions.